Is choline PET useful for identifying intraprostatic tumour lesions? A literature review. Issue 9 (September 2015) - Chan, Joachim; Syndikus, Isabel; Mahmood, Shelan; Bell, Lynn; Vinjamuri, Sobhan
Abstract : More than 80% of patients with intermediate-risk or high-risk localized prostate cancer are cured with radiation doses of 74–78 Gy, but high doses increase the risk for late bowel and bladder toxicity among long-term survivors. Dose painting, defined as dose escalation to areas in the prostate containing the tumour, rather than to the whole gland, minimizes dose to normal tissues and hence toxicity. It requires accurate identification of the location and size of these lesions, for which functional MRI is the current gold standard. Many studies have assessed the use of choline PET in staging newly diagnosed patients. This review will discuss important imaging variables affecting the accuracy of choline PET scans, how choline PET contributes to tumour identification and is used in radiotherapy planning and how PET can improve the patient pathway involving prostate radiotherapy. In summary, the available literature shows that the accuracy of choline PET improves with higher tracer doses and delayed imaging (although the optimal uptake time is unclear), and tumour identification by MRI is improved by the addition of PET imaging. We propose future research with prolonged choline uptake time and multiphase imaging, which may further improve accuracy.